2013
DOI: 10.1111/ijsw.12067
|View full text |Cite
|
Sign up to set email alerts
|

Increasing conflict in times of retrenchment? Attitudes towards healthcare provision in Europe between 1996 and 2002

Abstract: Public opinion is considered a major obstacle to changing the status quo of welfare state policies. Yet some far‐reaching reforms and gradual changes of European welfare states prompt the reverse question: Have increased reform pressures and restructuring efforts led to changes in individual attitudes? In line with previous research, I found that the strong support for a public provision of healthcare remains unchanged. But what about the structure of attitudes? Testing core assumptions of the new politics the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Another main interest of the present article concerns whether the above-mentioned societal cleavages have increased over time. Several studies have focused on ideological polarisation in the USA (DiMaggio, Evans, & Bryson, 1996;Evans, 2003), but few studies have investigated long-term trends in public opinion cleavages in Europe (Ebbinghaus & Naumann, 2017;Naumann, 2014;Svallfors, 2004Svallfors, , 2008. Studies in this research field have been restricted to healthcare and pension policies and have not found evidence that attitudes towards these two universal welfare programmes have become more polarised.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Another main interest of the present article concerns whether the above-mentioned societal cleavages have increased over time. Several studies have focused on ideological polarisation in the USA (DiMaggio, Evans, & Bryson, 1996;Evans, 2003), but few studies have investigated long-term trends in public opinion cleavages in Europe (Ebbinghaus & Naumann, 2017;Naumann, 2014;Svallfors, 2004Svallfors, , 2008. Studies in this research field have been restricted to healthcare and pension policies and have not found evidence that attitudes towards these two universal welfare programmes have become more polarised.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ebbinghaus and Naumann (2017) found no clear indication of increasing polarisation concerning spending for pensioners and unemployed individuals, but limited their analysis to Germany and the UK. Naumann (2014) found stable cleavages based on employment status, age, political ideology and health status concerning attitudes towards government responsibility for healthcare. Results by Svallfors (2004Svallfors ( , 2008 suggest persistent conflicts based on social class and age concerning welfare policies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With decreasing fertility rates and increasing life expectancy, Germany is one of the fastest aging countries in the world, and predictions show that the share of people aged 65 and older will increase from 21 percent in 2010 to 28 percent in 2030 [1]. The welfare state's financial sustainability is under pressure due to a growing number of beneficiaries and less contributors, and in particular, the public pension system is expected to face severe economic problems [2][3][4][5][6]. In reaction, German policy makers have introduced several far-reaching reforms with the aim of increasing the retirement age and, thus, relieve the pension system of financial pressure: They lifted the statutory retirement age from 65 to 67 [7], introduced training programs for older workers [8], and abolished early retirement pathways [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These patterns indicate a weak or ambiguous effect of welfare state context, at best. In the comparative literature, Naumann () also finds stable support of public health care and, more importantly, over‐time stability in the structure of conflict along the lines of social class, age and other socioeconomic characteristics on, despite institutional reforms. Note, however, that these studies do not provide a direct test of the context effects (e.g., effects of changing redistribution or institutional differences).…”
Section: Introductionmentioning
confidence: 99%